Estrategias discursivas. La prensa colombiana y la pobreza - Pardo Abril, Neyla Graciela (CIC. Cuadernos de Información y Comunicación, 2009)
This document is based on developments made in connection with the study of poverty representations in the Colombian press. It explores the phenomenon of discourse naturalization, regarding strategies commonly used in the press, to refer the issue of poverty. The central argument of this text points to the assertion that the poverty naturalization, namely, expressions that reflect poverty like a natural reality (living or inert), sometimes derives from use of two language resources: quantification and metaphor. Its common usage in the information reproduced by print media, influence the formation of meanings about the social phenomenon, which are embedded in the culture, guiding and determining ways of comprension and social action. The corpus analysed comprises two print media of national circulation (El Tiempo y El Espectador), which took the news between 1991 and 2006, they have in the holder, subholder, or abstract words poor, poverty, indigent, indigence, or those terms whose meaning subsumes the lexical units mentioned.